Production of polymer-bioactive glass nanocomposites for bone repair and substitution - Felgueiras, Helena Prado (2019)
Bioactive glass (BG) is a well suited biomaterial for bone and tissue regeneration. BG is capable of generating strong chemical interactions with the surrounding bone tissue and, by forming a calcium phosphate layer when exposed to physiological fluids, can promote osteointegration. Also, the ionic release from BG may stimulate gene expression and, thus, osteoinduction. Still, its use in biomedicine is limited by its poor mechanical performance. The combination with biodegradable polymers to form composites that explore the flexibility of these materials with the stiffness and bioactive character of the BG has opened a window to many more uses. Both synthetic and natural origin polymers have been combined with BG nanoparticles/nanofibers with successful outcomes. BG–polymer nanocomposites mimic more closely the structure of natural bone. In the present chapter we will enumerate the most promising BG–polymer combinations and the advantages introduced in bone regeneration by these composites, and will explore some of the most commonly used synthesis techniques applied to the production of BG–polymer composites.